PROFILE OF MATHEMATICAL COMMUNICATION’S ABILITY BASED ON LEVEL OF PROBLEM SOLVING’S ABILITY - Krisna Satrio Perbowo; Windia Hadi; Tuti Haryati (Prodi Pendidikan Matematika FKIP Universitas Madura, 2020)
Abstract : This study was aimed to define profile of mathematical communication based on the level of problem solving ability on secondary students. This study used mixed methods model with explanatory type. This sample used 30 secondary school students who was chosen based on teachers’ recommendation. The result shown that there are 16,67% students whose problem solving’s ability were placed on low level If we look on mathematical communication ability’s side, most of students faced on the diffulties of projecting figures into mathematical ideas. Students still made mistakes on calculating and the indicators was difficult when it stated to project any figures into mathematical ideas while the indicator that appear frequently was stated events or ideas in mathematical laguage. There are 70% students that whose problem solving ability were placed on medium level. If we look on mathematical conection ability most of information as shown unclearly and faced on difficulties when they summarize conclusion, they stated it into mathematical symbol. There are 13,33% students whose problem solving ability were pleced on high level and unclear to every single information that was told within solving strategy which directly on solving essentials. Keywords: Profile of mathematical Ability, Mathematical Communication, Problem Solving